Laboratory experiments for general, organic, and biochemistry - Betteheim, Frederichk A. (Thomson, 2007)
The 48 experiments in this well-conceived manual illustrate important concepts and principles in general, organic, and biochemistry. As in previous editions, three basic goals guided the development of all the experiments: (1) the experiments illustrate the concepts learned in the classroom; (2) the experiments are clearly and concisely written so that students will easily understand the task at hand, will work with minimal supervision because the manual provides enough information on experimental procedures, and will be able to perform the experiments in a 2 1/2-hour laboratory period; and, (3) the experiments are not only simple demonstrations, but also contain a sense of discovery